UPAYA ORANG TUA DALAM PEMBINAAN KEAGAMAAN ISLAM TERHADAP PELAJAR REMAJA DI MTSN 2 PAMEKASAN - Isbir, Moh.; Azhari, Jalaludin Faruk; Zubair, Asyhari (Jurnal Pendidikan Islam, 2023)
This consider points to decide the part of guardians in cultivating Islamic devout instruction in youths, models and imperatives, and arrangements for guardians in cultivating Islamic devout instruction in teenagers at MTsN 2 Pamekasan. This investigate was conducted at MTsN 2 Pamekasan. This investigate approach is subjective investigate. Whereas this sort of investigate is phenomenological inquire about. The comes about of the ponder appear that the part of guardians in cultivating Islamic devout instruction in youthful children can be said to have been carried out well. These parts incorporate: As teachers, guardians instill devout values, give exhortation based on devout lessons, and welcome their youth to carry out devout exercises such as congregational supplications, perusing the Koran, Yasin, and so on. From the comes about of the ponder, it was moreover found that there are impediments as well as arrangements for guardians. Imperatives incorporate: Frequently young people disregard their commitments as Muslims, disregard orders from their guardians, and regularly spend their time playing smartphones, recreations, and social media. Whereas the arrangements from guardians incorporate guardians continuously prompting young people to comply Islamic lessons and not disregard their commitments. When exhortation does not make young people have self-awareness, guardians will reprove them by hollering at them, rebuking and prompting them indeed more solidly.